Epidemiological aspects of carotid disease - Paljoskovska Jordanova Savetka (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2021)
Carotid artery disease most commonly manifests as atherosclerotic carotid artery disease, which can lead to an ischemic stroke. Our aim was to present the epidemiological aspects of carotid disease and to demonstrate the association of risk factors with carotid disease. For that purpose, we prospectively followed 1031 patients at the University Clinic for Cardiology in Skopje, who were examined for carotid stenosis and its correlation with risk factors such as hypertension, smoking, hyperlipidemia, diabetes, obesity and peripheral arterial disease. Results: Carotid stenosis was correlated with arterial hypertension, hyperlipidemia, diabetes mellitus, smoking, and peripheral arterial disease. Conclusions: Our study found that conventional risk factors such as hypertension, diabetes, smoking, and dyslipidemia were independently associated with significant carotid artery disease and peripheral arterial disease.